ANESTESIA DISSOCIATIVA EM POTROS PELA ASSOCIAÇÃO DE DROPERIDOL E QUETAMINA - Nunes, Newton [UNESP] (1992)
The aim of this work was evaluate the effect of droperidol associated to ketamine on some parameters as body temperature, heart rate, respiratory frequency, blood gases, pH eletrolites in foals. To 10 foals with 2 to 6 months average age and 50 to 210kg average weight was administered intravenously 0.8mg/kg, droperidol and 10 minutes after, by the same way, 2mg/kg, ketamine. The parameters were evaluated during 30 minutes at 10 minutes intervals, showing no significant differences, except the respiratory frequency and the body temperature that decreased during the experiment. The procedure can be used safely in foals.